2020
DOI: 10.1111/odi.13321
|View full text |Cite
|
Sign up to set email alerts
|

H‐type blood vessels participate in alveolar bone remodeling during murine tooth extraction healing

Abstract: Objectives We aimed to investigate whether skeletal‐specific H‐type blood vessels exist in alveolar bone and how they function in alveolar bone remodeling. Materials and Methods H‐type vessels with high expression of CD31 and Endomucin (CD31hiEmcnhi) were immunostained in alveolar bone. Abundance and age‐related changes in CD31hiEmcnhi endothelial cells (H‐ECs) were detected by flow cytometry. Osteoprogenitors association with H‐type vessels and bone mass were detected in tooth extraction model of alveolar bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 57 publications
(80 reference statements)
1
29
0
Order By: Relevance
“…This situation might be favored to induce intramembranous bone formation. In addition, intimate coupling of type H endothelium and osteoprogenitors was reported to be essential for bone metabolism and bone healing ( Kusumbe et al, 2014 ; Xu et al, 2018 ), and this coupling has also been observed in tooth extraction models in mice ( Yan et al, 2020 ). Further investigation to compare type H endothelium distribution and function among different bone healing models is of interest to understand the role of type H endothelium in bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…This situation might be favored to induce intramembranous bone formation. In addition, intimate coupling of type H endothelium and osteoprogenitors was reported to be essential for bone metabolism and bone healing ( Kusumbe et al, 2014 ; Xu et al, 2018 ), and this coupling has also been observed in tooth extraction models in mice ( Yan et al, 2020 ). Further investigation to compare type H endothelium distribution and function among different bone healing models is of interest to understand the role of type H endothelium in bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years growing body of evidence suggests that blood vessels in bone promote osteogenesis [10,11]. However, there are scarce data regarding the influence of barrier membranes on angiogenesis [12], pointing out the need for its research.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, type H vessels were confirmed in the alveolar bone and tooth extraction socket. ECs of subtype H and Runx2+ osteoprogenitor cells were detected and accumulated at the restoration stage, indicating the potential benefits of ECs of subtype H in bone regeneration ( Yan et al, 2020 ). Additionally, increased formation of type H vessels, consistent with enhanced bone healing, was observed during the treatment of fractures, whether by supplementation with recombinant SLIT3 or by low-intensity pulsed ultrasound ( Xu et al, 2016 ; Xu et al, 2018 ).…”
Section: Challenges and Prospectsmentioning
confidence: 99%